STUDENTS' PERCEPTION ABOUT FREQUENT EXAMINATIONS - Siddiqui, Rabia; Mannan, Nighat; Mannan, Fatima (Pakistan Journal of Physiology, 2017)
Background: A powerful way of improving one’s memory for study material is to be tested on that material. Frequent testing in the classroom may boost educational achievement at all levels of education. Repetitive evaluation of subject matter is called ‘frequent testing’. Methods: Data on perceptions of frequent assessment were collected from students of all five years of BUMDC, Karachi with a questionnaire. The 14 item questionnaire was clustered around 8 variables: the purpose, test content and objectives, timing, feedback on assessment, the assessor, frequent exams, understanding of curriculum, and test taking strategies. A 3 point itemized rating scale of ‘Yes’, ‘No’ and ‘Not sure’ was used for collecting responses. Students of all 5 years of MBBS of BUMDC were given the questionnaire forms and asked to complete them. Results: The study population consisted of 213 (64%) females and 120 (36%) males. Their mean age was 20±8 years. The most frequently endorsed purpose of assessment, as perceived by students was to achieve high grades. A second important purpose was motivation for learning. Conclusion: The underlying values of all these points are important to teachers and students seeking better ways to teach and learn. Frequent testing will enhance learning and studying habits, while increasing recall and the depth of knowledge learned. Keywords: Student, testing, questionnaire, examination, assessment, education, perception Pak J Physiol 2017;13(2):46–8